Correlation analysis of recurrent factors in borderline ovarian tumors undergoing fertility preservation surgery - Xie, Yichi; Wang, Dandan; Zhang, Ningning; Yang, Qing (Frontiers in Oncology, 2025)
ObjectiveTo explore the relapse - related factors of fertility preservation surgery for borderline ovarian tumors.MethodsPatients of childbearing age who underwent fertility preservation surgery for borderline ovarian tumors in Sheng jing Hospital of China Medical University from April 20 1 8 to April 20 2 3 were selected. Clinical data were collected and their clinical characteristics were statistically analyzed. It is to explore the risk factors of postoperative recurrence.ResultsA total of 30 8 patients were included in this study, of which 1 was lost to follow - up and 47 relapsed (4 7/3 0 7, 15. 3 1%). The results of multivariate analysis showed that the pathological features of micro papillary structure, intra operative as cites, bilateral tumors, and the increased ratio of neu tro phil to lymphocyte before surgery are independent risk factors for the recurrence of borderline ovarian tumors.ConclusionThe prognosis of women of childbearing age with borderline ovarian tumors undergoing conservation function surgery is good. However, patients with high - risk recurrence factors should be paid special attention and closely followed up after surgery.